Optimizing use of distiller’s grains with solubles (DGS) in finishing cattle diets - Loe, E.R.; Corrigan, M.E.; Quinn, M.J.; Depenbusch, Brandon E.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Rapid expansion of the fuel ethanol industry has increased availability of distillery byproducts. Distiller’s grains with solubles (DGS) are the predominant byproduct of fermenting grains to fuel ethanol. During this process, the majority of starch is removed from the grain, and residual components of the grain are concentrated into the distiller’s byproduct. Distiller’s grains with solubles contain the bran, which is high in fiber; the germ, which is high in fat; and the protein. Given the relatively high fiber content of DGS, it is conceivable that DGS could serve as a replacement for roughage in finishing diets. One of the major expenses incurred with production of distiller’s byproducts is the energy needed to dehydrate byproducts to acceptable moisture levels. Moisture content is critically important because it directly impacts transportation costs, storage characteristics, and handling properties of the feed. Dehydration of byproducts also may alter the nutritive value of the DGS. Generally speaking, extensive heating can result in the formation of indigestible complexes between carbohydrates and proteins, potentially reducing energy availability and efficiency of nitrogen utilization. Consequently, there is significant potential for creating differences in nutritional value of DGS as a result of drying. Corn and sorghum are the predominant grains used for ethanol production in the United States. The type of grain used is largely determined by the geographical location of the ethanol plant. For example, sorghum grain frequently is produced as a dryland crop in low rainfall areas of the Plains, and corn is produced in the High Plains and Corn Belt regions. In some regions, both corn and sorghum DGS may be available for use in livestock feeding; however, relatively little data is available pertaining to comparative nutritional values of DGS derived from corn and sorghum. The objectives of this study were to compare 1) sorghum-based DGS with corn-based DGS, 2) wet DGS with dry DGS, and 3) performance of cattle fed diets containing DGS with and without added roughage.
Keywords: Beef; Cattle; Distiller’s grains with solubles (DGS)